الضبط اللغوي وأثره في وضوح ألفاظ التفسير في كتاب الكامل للمبرد: دراسة وصفية تحليلية - الجندي، ناصر عبدالرحيم محمد عبدالرحيم (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بالإسكندرية, 2022)
هذا بحث بعنوان: "الضبط اللغوي، أنواعه، وآثاره في وضوح ألفاظ التفسير في كتاب الكامل للمبرد" دراسة وصفية تحليلية حيث تتناول الدراسة في هذا البحث: التعريف بالضبط، وبأنواعه، ثم بيان آثاره النحوية والصرفية في وضوح ألفاظ التفسير في كتاب الكامل، وقد اقتضت دراسة البحث أن يأتي في مقدمة، وتمهيد، ومبحثين، وخاتمة، وفهارس: * فالمقدمة: فيها تعريف بموضوع البحث، وأسباب اختياره، وخطة السير فيه. * والتمهيد: فيه دراسة موجزة عن: المبرد وكتابه الكامل. * أما المبحث الأول، فعن: "الضبط اللغوي، نشأته، وأنواعه، وآثاره" دراسة نظرية، وفيه ثلاثة مطالب: * أحدها: الضبط اللغوي، مدلوله، نشأته، وأسباب وضعه. * والثاني: أنواع الضبط اللغوي، وطرقه المستعملة. * والثالث: أهمية الضبط، وأبرز آثاره النحوية والصرفية. * والمبحث الثاني، عن: طرق الضبط عند المبرد، وأثر كل طريق في وضوح اللفظ المفسر في كتاب الكامل. Where the study in this research dealt with: the grammatical setting definition, and its types, then clarifying its grammatical and morphological effects in the clarity of the words of interpretation in the book of Al-Kamil. The study of the research required that it come in an introduction, a preface, two chapters, a conclusion, and indexes: The introduction contains definition of research topic, and the reasons for choosing it, and the plan to proceed it. And the preface: contains a brief study on: Al-Mubarrad and his book Al-Kamil. As for the first topic, it is about: “Languish Setting, its origin, types, and effects,” a theoretical study", and it contains three requirements: * The first: The Languish Setting, its meaning, its origin, and the reasons for its development. * The second: the types of Languish Setting and the methods used. * The third: the importance of Languish Setting, and its most prominent grammatical and morphological effects. * The second topic, is about: Methods of Setting to Al-Mubarrad, and the effect of each method on the clarity of the interpreted pronunciation in the book of Al-Kamil.
Keywords: تفسير القرآن -- اللغة العربية -- القواعد النحوية -- الصيغ الصرفية -- المبرد، محمد بن يزيد، ت. 296 هـ